Developing the competency of teaching children's literature for primary education students at some pedagogical universities in the Mekong delta region, Vietnam - Lan, Do Thi; Tuan, Tran Van (Edelweiss Applied Science and Technology, 2025)
The ability to teach children's literature is a vital component of the professional competencies required of primary school teachers. It plays a crucial role in fostering students’ language development, imagination, and moral values. Therefore, cultivating and enhancing this competency in students majoring in Primary Education is an essential and indispensable task in teacher training programs. This article, based on the application of modern scientific research methods—including literature review, field surveys, interviews, questionnaires, experimental research, and data analysis—proposes practical measures to develop teaching competencies for these students. The suggested measures target various stages of teacher education, such as designing evaluation criteria, organizing university-level instruction, implementing teaching practicum, engaging in internships, and conducting educational research. When applied consistently and flexibly, in alignment with real-world teaching and learning contexts, these solutions are expected to significantly improve the quality of children's literature instruction. Ultimately, they contribute to achieving the broader educational goals of primary schools in today’s evolving educational landscape.